Legal Protection of Children in Early Marriage Cases: An Islamic Law and Positive Law Perspective - Bunyamin Yafid; Nismayani B.; Muh. Idham (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the legal protection of children in cases of early marriage from the perspective of Islamic law and positive law in Indonesia. The main focus of this research is to find a meeting point between religious norms and national legal provisions in providing protection for children's rights. The method used is qualitative research based on library research with a normative-philosophical approach, examining both classical and contemporary Islamic literature, statutory regulations, and empirical data from relevant institutions. The findings show that although positive law has established a minimum age for marriage, its implementation still faces challenges due to legal loopholes, particularly through the marriage dispensation mechanism. Meanwhile, Islamic law, through the maq??id al-syar?‘ah approach, provides normative support for age restrictions for the sake of the child's well-being. Therefore, harmonizing these two legal systems is essential to build a more just, humanistic, and sustainable legal protection framework for children in Indonesia.